2013
DOI: 10.1159/000355669
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Life Space in Older Adults with Mild-to-Moderate Alzheimer's Disease Using Mobile Phone GPS

Abstract: Background: As an indicator of physical and cognitive functioning in community-dwelling older adults, there is increasing interest in measuring life space, defined as the geographical area a person covers in daily life. Typically measured through questionnaires, life space can be challenging to assess in amnestic dementia associated with Alzheimer's disease (AD). While global positioning system (GPS) technology has been suggested as a potential solution, there remains a lack of data validating GPS-based method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 28 publications
(49 reference statements)
3
108
4
Order By: Relevance
“…With regard to differences in physical function, previous studies showed that people with limited physical function lose opportunities to engage in physical and social activities, and are at higher risk of cognitive decline . Therefore, individuals with limited physical function could show further cognitive decline by failing to go outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to differences in physical function, previous studies showed that people with limited physical function lose opportunities to engage in physical and social activities, and are at higher risk of cognitive decline . Therefore, individuals with limited physical function could show further cognitive decline by failing to go outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported associations among life-space in community settings and physical performance, 25,26) cognitive function, 27) psychosocial factors, 28) concerns about falling, 29) and apathy. 26) Webber et al 30) presented a conical model of the theoretical framework for mobility in older adults.…”
Section: Associated Factors Of Life-space For the Elderly In Rokenmentioning
confidence: 99%
“…Although wandering and getting lost are a cause of both patient and caregiver stress [8], this must be balanced against the potential benefits in terms of physical exercise, social contact, informal supervision by neighbours and local shopkeepers and the perception of autonomy [9,10] afforded by what some social care organisations have termed “safe walking” [11,12]. Fear of getting lost is a contributor to the marked reduction in out-of-home mobility [13] and restricted life space [14] associated with cognitive impairment [15]).…”
Section: Introductionmentioning
confidence: 99%